2016
DOI: 10.1007/s11678-016-0386-9
|View full text |Cite|
|
Sign up to set email alerts
|

Subacromial spacer implantation for massive rotator cuff tears

Abstract: BackgroundMassive rotator cuff tears (MRCT) can be treated arthroscopically by partial reconstruction, tenotomy/tenodesis of the long head of the biceps, and debridement. A new treatment option is the additional implantation of a biodegradable spacer (InSpace Balloon®; ISB) into the subacromial space, which reduces subacromial shear forces to keep the humeral head centered in the glenoid. The aim of this study is to investigate the clinical outcome of patients with MRCT who were treated arthroscopically with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 15 publications
1
54
1
Order By: Relevance
“…One retrospective non-randomised study of 23 patients (12 with the balloon) showed an improvement in outcomes compared with debridement alone. 27 There are no completed RCTs.…”
Section: Open Accessmentioning
confidence: 99%
“…One retrospective non-randomised study of 23 patients (12 with the balloon) showed an improvement in outcomes compared with debridement alone. 27 There are no completed RCTs.…”
Section: Open Accessmentioning
confidence: 99%
“…The implanted balloon allows for frictionless gliding of the humeral head in the subacromial space and reduces pain, ultimately restoring the biomechanics of the glenohumeral joint. 65 66) …”
Section: Biodegradable Subacromial Spacer Insertionmentioning
confidence: 99%
“…The spacer deflates iñ10 weeks and completely degrades within 15 months,30 a sufficient period of time to perform physiotherapy program. It is not clear why pain and functional scores continue to improve beyond the period of spacer disintegration.…”
Section: Subacromial Biodegradable Spacermentioning
confidence: 99%